1994
DOI: 10.1246/cl.1994.855
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of CO2 with H2O on TiO2(100) and TiO2(110) Single Crystals under UV-irradiation

Abstract: The reduction of CO2 with H2O was investigated on the single crystals of TiO2(100) and TiO2(110); the former TiO2(100) exhibiting a higher efficiency in the formation of CH4 and CH3OH than TiO2(110). Measurements of the intermediate species formed on the TiO2(100) single crystal were carried out using a high resolution electron energy loss spectroscopy (HREELS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 7 publications
1
48
0
Order By: Relevance
“…Although the reasons for this opposite behavior have not been analysed yet, these results show the influence that the morphology of TiO 2 has on its photocatalytic activity. 131,132 In this regard, a recent publication has shown that anatase TiO 2 nanorods loaded with platinum are more efficient than the analogous P25 sample for the photocatalytic CO 2 reduction to CH 4 in the presence of H 2 O vapor. 103 Although the initial reaction rates for the TiO 2 nanorods and P25 are not that different, it is the long term photoactivity of TiO 2 nanorods which is affected with respect to P25.…”
Section: Metal Nanoparticles Supported On Titania As Photocatalystsmentioning
confidence: 99%
“…Although the reasons for this opposite behavior have not been analysed yet, these results show the influence that the morphology of TiO 2 has on its photocatalytic activity. 131,132 In this regard, a recent publication has shown that anatase TiO 2 nanorods loaded with platinum are more efficient than the analogous P25 sample for the photocatalytic CO 2 reduction to CH 4 in the presence of H 2 O vapor. 103 Although the initial reaction rates for the TiO 2 nanorods and P25 are not that different, it is the long term photoactivity of TiO 2 nanorods which is affected with respect to P25.…”
Section: Metal Nanoparticles Supported On Titania As Photocatalystsmentioning
confidence: 99%
“…GC analysis of the products showed predominantly methane, along with ethane, propane, and butane as minor products. [30] Also, control experiments show that there is no appreciable hydrocarbon production in the absence of either solar irradiation or photocatalysts, indicating that there are no significant thermal or photon effects, respectively. The CuO-TiO 2Àx N x hollow nanocubes yield 41.3 ppm g À1 h À1 of methane, which represents a production rate that is 2.5 times faster than that of Degussa P25 TiO 2 when measured under the same conditions (16.2 ppm g À1 h À1 ).…”
mentioning
confidence: 99%
“…Since the successful works in 1979 by Fujishima et al1 to report the photoelectrocatalytic reduction of CO 2 to form organic compounds such as formic acid, formaldeyde, methyl alcohol and methane, in the presence of photosensitive semiconductor powders suspended in water as catalysts, many studies have been focused on the modification of TiO 2 in order to exploit its application to the CO 2 photoreduction234567. As an ideal photocatalyst, nanoscaled TiO 2 was widely used in the photodegradation of organic pollutants89, due to its inexpensive, non-toxic, high stability, and other advantages10111213.…”
mentioning
confidence: 99%